Evaluation of the heart rate during initial active standing in patients with vasovagal syncope - Jose Del Carmen Iglesias Alfonso; Barbaro Nicolas Socarras Hernandez (Revista Cubana de Medicina Militar)
Introduction: Vasovagal syncope is the most frequent cause of brief loss of consciousness, in its etiopathogenesis an autonomic dysfunction is reported that can be manifested in immediate active standing. Objective: To compare the dynamics of heart rate changes during immediate active standing of patients suffering from vasovagal syncope with control subjects. Methods: 132 supposedly healthy subjects (group A) between 18 and 25 years old and 156 patients with vasovagal syncope were evaluated, which were divided by their response to prolonged standing, negative 111 (group B) and positive 45 (group C). Electrocardiographic activity was recorded in the supine position and at the beginning of active standing, the sequences of RR intervals were obtained. The heart rate was compared in the 3 groups, using 22 indicators (positional, temporal, ordinal and relational, average and of the speed of changes). Results: Differences were not found in the average indicators in the analyzed period, however, some that evaluate the speed of the initial change were significantly lower in group A compared to B and C (p<0.05), while others that evaluate the speed recovery rates were significantly lower in group C compared to A and B. This allows to characterize, compare and differentiate the groups studied during the complex and rapid interactions that occur in the change of position. Conclusion: The dynamic of frequency changes, allowed to find indicators, which can be considered as possible predictors of an inadequate cardiovascular response in patients with vasovagal syncope.